IMPLEMENTASI KOLABORASI MODEL PENTAHELIX DALAM RANGKA MENINGKATKAN PEMBERDAYAAN UMKM EX LOKALISASI DOLLY PADA MASA PANDEMI COVID 19 (Studi Kasus DS.Point) - Supriyanto Supriyanto; Fredy Iskandar (Governance, JKMP (Governance, Jurnal Kebijakan & Manajemen Publik), 2022)
After the closing of Dolly's localization in 2014, the Surabaya city government has purchased several guesthouses in Dolly and converted them into various kinds of craft production sites. The location which was previously a place of prostitution with the largest income in Southeast Asia was later turned into the largest MSME center in Surabaya. The Surabaya government continues to provide assistance to residents of EX Localization in order to create a better image, namely by inviting local community members to become MSME actors. DS.Point (Dolly Saiki Point) is a silent witness to the dark history of the City of Surabaya, but has now been designated by the Surabaya City Government as an area for commercial, economic, and tourism activities. DS.Point (Dolly Saiki Point) is under the auspices of the Surabaya City Food and Agriculture Security Service, which makes it a souvenir center that accommodates processed products or products from MSME activists from residents of EX Lokaliasai Dolly. The research method used is descriptive qualitative which refers to the identification of distinguishing traits or characteristics of a group of people, objects, or events in order to provide an overview of the Implementation of the Pentahelix Model Collaboration in the Context of Improving the Empowerment of MSMEs Ex Dolly Localization During the Covid-19 Pandemic. Data collection techniques were carried out through the process of observation, interviews and documentation. The theory used is Collaborative Governance. The results of the study show that the roles played by the penta helix actors are quite good and the collaboration created between them has been going well, this can be seen by the inability for the actors to stand alone in increasing the empowerment of SMEs Ex Dolly Localization. This also has a good impact on the perpetrators of the Ex Dolly Localization MSMEs under the auspices of DS Point (11pt, single line spacing, 1 paragraph).